ANALISIS HEAT TRANSFER COEFFICIENT SEBELUM DAN SESUDAH OVERHAUL PADA ECONOMIZER BOILER DI PT. JAPFA COMFEED BANJARMASIN - Muhammad Ramlan; Aqli Mursadin (JTAM ROTARY, 2019)
In some heat exchanger tools are widely used in industries such as power plants, oil refineries, chemical plants and petrochemicals, natural gas industry, refrigeration, and so forth. One example of a heat exchanger found in the poultry feed industry in PT.Japfa Comfeed Branch of Banjarmasin is the economizer, where the hot vapor of combustion in the furnace is used as a feed water heater before entering the boiler. From the results of the study known in the economize coefficient of the highest heat transfer before the overhaul of 1.393.1 Btu / jam.ft2.oF at 92.5 oC, and the lowest heat transfer coefficient before the overhaul of 1,334.8 Btu / jam.ft2. oF at 101 ° C. after the overhaul, it is known that the highest economizer heat transfer coefficient is 1,419.7 Btu / hour.ft2.oF at 99oC, and the lowest heat transfer coefficient after the overhaul is 1,378.6 Btu / hr.ft2.oF at 104.5 oC. The increase in heat transfer coefficient value after overhaul is 6.4% of the heat transfer coefficient before overhaul. Keywords: Economizer, Boiler,  Heat Transfer Coefficient